Dıstrıbutıon Of The Oral Candıda Incıdence Accordıng To The Sex And Cıty-Localızatıon In Young Adult Before Orthodontıc Treatment In The Regıon West-Medıterranean - Aynur Medine Şahin Sağlam; Hüseyin Karayılmaz; Selçuk Kaya; Birdal Yorgancıgil (Galenos Yayinevi, 2002)
The aim of this study, is to examine the orthodontic patients for the carrier incidence of Candida and to determine the effects of geographical and gender differences to the Candida incidence. One hundred and nine children, who do not have any systemic disease, who were not treated with removable orthodontic appliances before, who do not smoke, were investigated. As a result of this study, the incidence of Candida was %28.44 and the most three identifed Candida species were C. Albicans, C. Tropicalis and C. Guillermondii. As an istatisticaly, no significant differences were found in Candida incidence between the patients living in İsparta, Antalya and Burdur. Furtennore there is no significant difference between genders.